Displacement and Family Separation of Australian Aborigines as Depicted in Memoirs of Stolen Generation - POPIŃSKA-PINDYCH, Aleksandra (Transfer. Reception Studies, 2019)
The treatment of indigenous tribes during the colonization of Australia has always been a subject widely discussed and analysed. Nevertheless, the way in which Australian Aboriginal people were forced to migrate within Australia and how the government executed the brutal plan of separating indigenous children from their families and homeland is a unique phenomenon. The trauma of displacement still exerts a dramatic impact on generations of indigenous people as their well-being results from their interaction with the land of their ancestors. The aim of this article is to familiarise the reader with the history of Aboriginal trauma through the analysis of their testimonials and memoirs collected by a governmental committee for the sake of publishing the "Report of the National Inquiry into the Separation of Aboriginal and Torres Strait Islander Children from Their Families". It is hardly possible to employ any contemporary theory of trauma in this analysis, but the author’s findings have undeniably factual value.